Percentilar Model or normality for behavior weight gain of maternal according to maternal height by gestational age - Antón Pérez, Juan Manuel (2016)
This research aims to build the normality percentile model of gain behavior in the maternal weight according to breast size for gestational age, in order to malee clinical diagnostics valid, rapid and zero cost of pregnant intrauterine growth from the third trimester of pregnancy. The sample stratified by size was composed of 936 pregnant women with single fetus with normal intrauterine growth and who attended the Health Center Pimentel District in the period 2011-2013, and 90 women pregnant of single fetus with any intrauterine growth from April to May 2014. For this purpose, maternal weight gain's percentile curves were built according to the gestational age, in general and per the pregnant woman's size, with which diagnoses of the intrauterine growth were take in 90 singleton gestations' pregnant women with any intrauterine growth. These were also compared with the diagnose given by the expert physician. After comparing, the general normality percentile model prepared by the authors presented a Sensitivity (84.62%}, Specificity (93.75%}, Predictive Value of Positive Test (84.62%), and Predictive Value of Negative Test (93.75%}, superior or equal to the required level (80%) in the study hypothesis.